1999
DOI: 10.1016/s0378-1097(99)00264-5
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric investigation of heterogeneous copper-sensitivity in asynchronously grown Saccharomyces cerevisiae

Abstract: The variable stress-sensitivity of individual cells within pure cultures is widely noted but generally unexplained. Here, factors determining the heterogeneous susceptibility to copper toxicity in Saccharomyces cerevisiae were examined with a rapid nonperturbing approach based on flow cytometry. By determination of the DNA content (with propidium iodide) in cell fractions gated by forward angle light scatter (an indicator of the cell volume), it was shown that forward angle light scatter measurements gave an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…1a). Previous results on DNA distributions (Howlett & Avery, 1999 ;Fortuna et al, 2000) showed that these regions are related to the different phases of the cell cycle ; the A, B and C gated regions correspond to cells in phases G0\G1, S and G2\M, respectively. The fluorescence obtained in each gated region gives rise to three different distributions (Fig.…”
Section: Normalized Rh123 Fluorescencementioning
confidence: 91%
“…1a). Previous results on DNA distributions (Howlett & Avery, 1999 ;Fortuna et al, 2000) showed that these regions are related to the different phases of the cell cycle ; the A, B and C gated regions correspond to cells in phases G0\G1, S and G2\M, respectively. The fluorescence obtained in each gated region gives rise to three different distributions (Fig.…”
Section: Normalized Rh123 Fluorescencementioning
confidence: 91%
“…Cells were grown in YPAD to a density of 5 ϫ 10 6 to 10 ϫ 10 6 cells/ml at 25°C and incubated at 37°C for 3 h. Culture samples corresponding to 10 7 cells were washed in 1 ml of 0.2 M Tris-HCl (pH 7.5), fixed in 1 ml of 0.2 M Tris-HCl (pH 7.5) containing 70% ethanol, washed in 1 ml of 0.2 M Tris-HCl (pH 7.5), dissolved in 1 ml of 0.2 M Tris-HCl (pH 7.5) containing 0.25 mg of RNase A (Wako)/ml, incubated at 50°C for 1 h, mixed with 20 l of 50-mg/ml proteinase K (Wako), incubated at 50°C for 1 h, pelleted by centrifugation at 10,000 ϫ g for 2 min, dissolved in 1 ml of 0.2 M Tris-HCl (pH 7.5) containing 16 g of propidium iodide/ml, incubated at room temperature for 30 min in a dark room, sonicated, and analyzed by flow cytometry (Coulter; Epics Elite ESP) (13).…”
Section: Methodsmentioning
confidence: 99%
“…b. Effect of cell cycle - Howlett and Avery (1999) investigated the relationship between the cell volume (as the volume of the cells vary during the cell cycle) and the susceptibility to copper toxicity in Saccharomyces cerevisiae. The correlation between the cell volume (by examining the forward angle light scatter -FSC) and the cell cycle stage (by examining the DNA content) indicated that the largest (the cells about to undergo mitosis) were most resistant to Cu and the smallest (newly divided cells) cells were also relatively resistant to copper.…”
Section: Effect Of Heavy Metals On Bioremediationmentioning
confidence: 99%